2008
DOI: 10.1111/j.1365-313x.2008.03585.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Senescence‐associated vacuoles’ are involved in the degradation of chloroplast proteins in tobacco leaves

Abstract: SummaryMassive degradation of photosynthetic proteins is the hallmark of leaf senescence; however the mechanism involved in chloroplast protein breakdown is not completely understood. As small 'senescence-associated vacuoles' (SAVs) with intense proteolytic activity accumulate in senescing leaves of soybean and Arabidopsis, the main goal of this work was to determine whether SAVs are involved in the degradation of chloroplastic components. SAVs with protease activity were readily detected through confocal micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
151
0
38

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(194 citation statements)
references
References 52 publications
5
151
0
38
Order By: Relevance
“…Many membrane-bound carriers that deliver plastid contents to the vacuole for degradation during leaf senescence have been characterized. The RECA-GFP bodies seen in chmp1 cells morphologically resemble Rubiscocontaining bodies (RCBs) and senescence-associated vacuoles previously documented to arise during leaf senescence and proposed to help transport stromal contents like Rubisco and RECA-GFP to the vacuole for breakdown (Chiba et al, 2003;Martínez et al, 2008), but appear distinct from the much smaller ATI1-PS bodies (50 to 100 nm) (Michaeli et al, 2014). Our results indicate that not only stromal but also envelope proteins such as MEX1-YFP become incorporated into these bodies.…”
Section: The Chmp1 Mutant Accumulates Cytoplasmic Bodies With Plastidmentioning
confidence: 69%
See 1 more Smart Citation
“…Many membrane-bound carriers that deliver plastid contents to the vacuole for degradation during leaf senescence have been characterized. The RECA-GFP bodies seen in chmp1 cells morphologically resemble Rubiscocontaining bodies (RCBs) and senescence-associated vacuoles previously documented to arise during leaf senescence and proposed to help transport stromal contents like Rubisco and RECA-GFP to the vacuole for breakdown (Chiba et al, 2003;Martínez et al, 2008), but appear distinct from the much smaller ATI1-PS bodies (50 to 100 nm) (Michaeli et al, 2014). Our results indicate that not only stromal but also envelope proteins such as MEX1-YFP become incorporated into these bodies.…”
Section: The Chmp1 Mutant Accumulates Cytoplasmic Bodies With Plastidmentioning
confidence: 69%
“…Through these receptors, autophagosomes selectively engulf peroxisomes (pexophagy), mitochondria (mitophagy), endoplasmic reticulum (reticulophagy), RNAs (RNautophagy), ribosomes (ribophagy), and other cellular components. Chloroplast dismantling during senescence also involves the delivery of chloroplastic constituents to vacuoles for degradation (Chiba et al, 2003;Martínez et al, 2008;Ono et al, 2013). ATG8-decorated bodies containing Rubisco and other stromal proteins accumulate in the vacuolar lumen of wild-type Arabidopsis plants but not in autophagy mutants Wada et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Otegui et al 110 and Martínez et al 111 found bodies other than RCBs in senescent cells containing chloroplasts. It was suggested that these bodies, called senescence-activated vacuoles (SAVs), are different from RCBs, since they show chlorophyll autofluorescence, which is not observed in RCBs.…”
Section: Autophagy During Internal Degradation Of Chloroplasts and Otmentioning
confidence: 99%
“…101 The SAVs contain Rubisco as well as SAG12, a specific senescence-associated cysteine protease. 110 Martínez et al 111 showed intense proteolytic activity in SAVs. Protease inhibitors delay the decrease in Rubisco levels in isolated SAVs held at 30 °C.…”
Section: Autophagy During Internal Degradation Of Chloroplasts and Otmentioning
confidence: 99%
“…Substrate proteins must be transported and sequestered into these lytic vacuoles before degradation. Therefore, senescence-associated vacuoles are lytic vacuoles and involved in the degradation of imported chloroplast proteins in tobacco leaves (Martı´nez et al, 2008). The molecular mechanisms for vacuolar protein degradation and nutrient recycling pathway in senescent leaves are generally not clear.…”
Section: Introductionmentioning
confidence: 99%